Investigating Household Factors and Child Physiognomies as Predisposing Dynamics to Optimal Breastfeeding among Fertile Mothers in West Africa: A Multilevel Study - Taofik Olatunji Bankole; Glory Urhere; Abiodun Oluwaseun Oyebode (European Scientific Journal, ESJ, 2020)
Background In many West African countries, the vulnerability of infants and under-five children to life threatening infections, poor physiological development, cognitive impairments and mortality, due to their weak immune system has been extensively related to the non-adherence of mothers to optimal breastfeeding. Earlier studies had inspected and explored the conceivable predictors of the non-conformity of mothers in the region to the recommended breastfeeding practices by UNICEF/WHO. However, these empirical studies had neither investigated the joint effect of household factors and child physiognomies nor adopted the multilevel method across countries in West Africa. The study addresses this limitation by investigating the identified explanatory variables as predisposing dynamics to optimal breastfeeding among fertile mothers in three selected West African countries Method This study was a cross-sectional multilevel survey. It analysed secondary quantitative data extracted from the Demographic Health Surveys conducted in Guinea (2012 GDHS), Nigeria (2013 NDHS) and Sierra Leone (2013 SLDHS). Information was sourced from a weighted sample size of 12,180 (NDHS), 5,008 (SLDHS), and 3,082 (GDHS) for fertile mothers aged 20-49 years old, who have had at least a birth prior the surveys. The response variable was optimal breastfeeding practice. It was captured by adherence and non-adherence to it thus, it was dichotomised into “1” if adhered to by fertile mothers and “0” if otherwise. The explanatory variables were household factors and child physiognomies and were measured at individual and community levels. The fixed and random effect logistic regression was carried out using Stata 14. Results Results showed that < 10% of fertile mothers practiced optimal breastfeeding in Guinea (5.3%), and Nigeria (8.6%), while only 14% of fertile mothers in Sierra Leone adhered to the practice. The fixed effect results showed that household factors, child physiognomies, and maternal factors at community level were significantly associated with optimal breastfeeding (p<0.05). the random effect results showed that household factors at community level accounted for 29.0%, 23.6% and 23.3% variation in adherence to optimal breastfeeding in Guinea, Nigeria, and Sierra Leone respectively. Results showed that child characteristics, at community level contributed 36.3%, 20.6% and 18.7% variation in adherence to optimal breastfeeding by fertile mothers in Guinea, Nigeria, and Sierra Leone respectively. Results, further showed that household factors and child physiognomies, at the community level jointly accounted for 20.4%, 21.5%, and 19.85 variation in adherence to optimal breastfeeding by fertile mothers in Guinea, Nigeria, and Sierra Leone respectively. Conclusion The study concluded that adherence of fertile mothers to optimal breastfeeding is fundamental to reducing the vulnerability of infants and young children to life threatening infections, poor physiological and cognitive impairments, and early childhood death to the lowest in Guinea, Nigeria, Sierra Leone, and the sub-region of West Africa as a whole.